Enhancing Vocational High School Students' Fieldwork Practical Report Writing Through Project-Based Learning with Audiovisual Media - Adliza Adliza; Tressyalina Tressyalina (STAI Hubbulwathan Duri, 2025)
This study examines the effectiveness of the Project-Based Learning (PjBL) model supported by audiovisual media in improving vocational high school students' fieldwork practical (PKL) report writing skills. It also explores the role of students' reading interest in mediating these outcomes. A quasi-experimental design with a pre-test–post-test control group was employed. The study involved 79 11th-grade students from SMK Negeri 7 Batam, divided into an experimental group (n=40) taught using PjBL with audiovisual media, and a control group (n=39) taught using conventional visual media. Data were collected through a PKL report writing test and a reading interest questionnaire. Statistical analyses included the Lilliefors test for normality, F-test for homogeneity, and two-way ANOVA to test hypotheses. The experimental group outperformed the control group, achieving a higher mean score (84.700 vs. 70.154). Data were confirmed to be normally distributed and homogeneous. Hypothesis testing showed that the PjBL model with audiovisual media significantly improved PKL report writing skills across both high and low reading interest groups (p 0.05). Additionally, a significant interaction effect was found between the learning model and reading interest (F = 4.899, p 0.05). The findings support the integration of PjBL with audiovisual media as an effective instructional strategy for enhancing report writing skills, particularly in vocational education. It also highlights the importance of considering students' reading interest to optimize learning outcomes.